2020
DOI: 10.1021/acsenergylett.0c01566
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Surface Engineering on SnO2 Reduces Energy Loss in Perovskite Solar Cells

Abstract: Tin oxide (SnO2) has recently emerged as a promising electron transport layer for perovskite solar cells (PSCs) in light of the material’s optical and electronic properties and its low-temperature processing. However, SnO2 films are prone to surface defect formation, which results in energy loss in PSCs. We report that surface treatment using ammonium fluoride (NH4F) leads to reduced surface defects and that it also induces chemical doping of the SnO2 substrate simultaneously. The effects of NH4F treatment on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
274
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(279 citation statements)
references
References 23 publications
5
274
0
Order By: Relevance
“…In addition, Figure 1b shows that Sn 3d peak shifts by about 0.3 eV towards a lower binding energy for the SnO 2 ‐RbF, indicating a change in electron cloud density around the Sn atoms because of the strong bonding between F and Sn when RbF is introduced into the bulk SnO 2 . [ 39,40 ] However, the Sn 3d peak of the SnO 2 /RbF shows almost no shift compared with the SnO 2 film, which implies the weak interaction between F and Sn atoms. This phenomenon indicates that the FSn bond may form before or during the annealing process, after that SnO 2 has crystalized and could hardly interact with F ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Figure 1b shows that Sn 3d peak shifts by about 0.3 eV towards a lower binding energy for the SnO 2 ‐RbF, indicating a change in electron cloud density around the Sn atoms because of the strong bonding between F and Sn when RbF is introduced into the bulk SnO 2 . [ 39,40 ] However, the Sn 3d peak of the SnO 2 /RbF shows almost no shift compared with the SnO 2 film, which implies the weak interaction between F and Sn atoms. This phenomenon indicates that the FSn bond may form before or during the annealing process, after that SnO 2 has crystalized and could hardly interact with F ions.…”
Section: Resultsmentioning
confidence: 99%
“…However, more and more groups found that the hysteresis still existed in the SnO 2 ‐based (commercial SnO 2 aqueous colloidal dispersion) PSCs unless modifying the SnO 2 surface or adding additives into the SnO 2 . [ 36–39 ] For example, Facchetti and co‐workers found non‐conjugated multi‐zwitterionic small‐molecule electrolytes could modify the SnO 2 /perovskite interface to passivate defects/traps and further restrain the non‐radiative recombination, which decreased its voltage loss and eliminated the hysteresis. [ 36 ] In addition, Zhang and co‐workers reported graphdiyne introduction into SnO 2 efficiently assisted perovskite crystallization, contributing to high‐quality perovskite films with a lower defect density.…”
Section: Introductionmentioning
confidence: 99%
“…After optimization, the best device (0.1cm 2 ) is obtained with a PCE of 23.17%, a V OC as high as 1.126 V, a J SC of 24.9 mA cm −2 , and FF of 82.5%. It is one of the best performances in PSCs with modified SnO 2 [ 15 , 51 , 52 ]. The superior performance of PSCs with cPCN-treated SnO 2 is in line with the improved film quality and higher absorptions.…”
Section: Resultsmentioning
confidence: 99%
“…[ 24 ] Jung et al used NH 4 F surface treatment to reduce the defect sites on the SnO 2 surface and obtained a higher PCE. [ 15 ] Furthermore, Liu et al modified SnO 2 by ethylene diamine tetra‐acetic acid (EDTA) chelating agent to realize an EDTA‐complexed SnO 2 ETL, which shows more superior electronic properties than the pristine SnO 2 ETLs. [ 26 ] However, the effect of defect passivation is limited owing to the weak interaction between the passivation molecules and the SnO 2 NCs, resulting in the agglomeration of SnO 2 NCs still exists.…”
Section: Introductionmentioning
confidence: 99%